FORMATION OF A PROJECT ACTIVITY MANAGEMENT SYSTEM IN THE AGRO-INDUSTRIAL COMPLEX OF THE REGION - Tatyana CHUVORKINA; Oksana KADIKOVA; Antonina SHATOVA; Natalia SOLOGUB; Alexander RUDYAKOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Modern challenges, limitations and risks of the socio-economic development of the region's agro-industrial complex require concentration of efforts, finances, managerial competencies in strategically important areas and tasks. The basis for the effective functioning of the agro-industrial complex of the Penza region is the application of the principles of project management in the activities of agribusiness entities. Project management is a tool both for managing the creation of new products and services, and for implementing targeted changes within individual organizations, as well as entire socio-economic systems. In the Penza region, project management is widely used by agribusiness entities in the implementation of both large and local projects in various fields of activity. The paper presents the results of the analysis of project management in the agro-industrial sector of the region, which indicates both positive and negative trends. The identified problems indicate a low level of quality of the processes of initiation and planning in the project management of business entities. In the current research the system of project management of agribusiness is considered taking into account state support. As a result of the analysis of the relevant projects, the main directions for improving the elements of project management were identified. In the frame of the current research the following research methods were used: the analogy method, the abstract-logical and analytical methods, the method of comparative legal assessment.